Cryptography, Information Theory, and Error-Correction: A handbook for the 21st century - Bruen, Aiden A.; Forcinito, Mario A. (USA: Wiley Interscience, 2005)
With identity theft, cybercrime, and digital file sharing proliferating in today's wired world, providing safe and accurate information transfers has become a paramount concern. The issues and problems raised in this endeavor are encompassed within three disciplines: cryptography, information theory, and error-correction. As technology continues to develop, these fields have converged at a practical level, increasing the need for a unified treatment of these three cornerstones of the information age. This book offers a complete, yet accessible account of the technologies shaping the 21st century. This new edition is geared towards audiences from financial institutions, banks, law companies and governments interested in blockchains, and companies using security for new products such as self-driving cars. This new edition also features five new chapters on security and the internet of things, increased security in elliptic curve cryptography, some new equalities in information theory, blockchains and cryptocurrency, and Bletchley Park.